EVALUATION OF USABILITY OF MAPS OF DIFFERENT SCALES PRESENTED IN AN IN-CAR ROUTE GUIDANCE AND NAVIGATION SYSTEM - Ramos, Ana Paula Marques; Pugliesi, Edmur Azevedo; Oliveira, Renan Furlan de; Tachibana, Vilma Mayumi; Decanini, Mônica Modesta Santos (Boletim de Ciências Geodésicas, 2018)
Noise from the information communication process produced by the interfaces of navigation systems has overloaded drivers’ cognitive processing systems and increased the probability of traffic accidents. This work evaluates the usability of maps of different scales in a prototype route guidance and navigation system. The maps were designed on basic cartographic communication principles, such as perceptive grouping and figure-ground segregation, as well drivers’ requirements for performing a tactical task. Two different scales were adopted, 1:3,000 and 1:6,000, and the maps implemented in the prototype. A total of 52 subjects (26 males and 26 females) participated in an experiment performed in a driving simulator. The maps describe an urban route composed of 13 simple and complex maneuvers. The drivers’ mental workload was measured in terms of visual demand, navigational error and subjective preference. Results reveal that the usability of maps is influenced by map scale variation, and this is related to maneuver complexity. Also, an association between drivers’ visual demand and gender was found, and this was related to drivers’ spatial ability. More implications are presented and discussed.